Analysis of Private Transfers with Panel Fixed Effect Censored Model Estimator - KANG, Sung Jin (Institutional Knowledge at Singapore Management University, 2003)
Understanding private transfer is important for safety-net policies because private transfer provides economic benefits similar to those of public programs such as unemployment insurance and pension. Applying Honoré’s [Econometrica 60 (1992) 533] panel fixed-effect censored model estimator to Korean data, we show that private transfer is altruistically motivated and there is a strong crowding-out effect of public transfer on private transfer. We also find that low-income people suffered to different degrees during the financial crisis period of 1997 to 1998. This finding and the crowding-out effect may be taken as failures of the Korean public transfer programs during the period.